2015
DOI: 10.1007/s10869-015-9428-3
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Conspiracy Beliefs: Implications for Leadership Styles and Employee Outcomes

Abstract: PurposeBelief in conspiracy theories about societal events is widespread among citizens. The extent to which conspiracy beliefs about managers and supervisors matter in the micro-level setting of organizations has not yet been examined, however. We investigated if leadership styles predict conspiracy beliefs among employees in the context of organizations. Furthermore, we examined if such organizational conspiracy beliefs have implications for organizational commitment and turnover intentions.Design/Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 63 publications
(101 reference statements)
2
47
0
Order By: Relevance
“…This study first aimed to corroborate the finding that organizational conspiracy belief is correlated with turnover intentions (see Van Prooijen & de Vries, ). Going further, we also tested the mechanisms that may be responsible for this association.…”
Section: Studymentioning
confidence: 81%
See 4 more Smart Citations
“…This study first aimed to corroborate the finding that organizational conspiracy belief is correlated with turnover intentions (see Van Prooijen & de Vries, ). Going further, we also tested the mechanisms that may be responsible for this association.…”
Section: Studymentioning
confidence: 81%
“…Further, Van Prooijen and de Vries () found that organizational commitment was associated with belief in workplace‐related conspiracies and that it mediated the association between organizational conspiracy belief and turnover intentions. It remains to be seen whether organizational conspiracy belief exerts a causal influence on organizational commitment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations